PERANCANGAN PERANGKAT LUNAK PEMBELAJARAN SIMULASI JARINGAN KOMPUTER DENGAN MENERAPKAN METODE CAI - Sony Bahagia Sinaga; Satria Yudha Prayogi (Fakultas Teknik Universitas Islam Sumatera Utara, 2023)
The development of computer technology is increasing rapidly, this can be seen in the era of the 80s computer networks are still a puzzle that academics want to answer, and in 1988 computer networks began to be used in universities, companies, now entering the era of this millennium, especially the world wide internet, has become the daily reality of millions of people on this earth. In addition, network hardware and software have completely changed. At the beginning of its development, almost all networks were built from coaxial cable, now many of them are built from fiber optics or wireless communication. With the development of computer and communication technology, a single computer model that serves all the computational tasks of an organization has now been replaced by a set of computers that are separate but interconnected in carrying out their duties, a system like this is called a computer network. In learning computer networks the delivery of conventional learning material is felt to be less able to increase student learning interest. This paper will discuss the creation of computer-based learning applications where the delivery of material is carried out using the CAI (Computer Assisted Instruction) method and the material presented is about the basics of computer networks, in the process presented in the form of materials, exercises and simulations. The purpose of the research to be achieved is to explain how to assemble a computer network using learning simulations to be understood by students. The conclusions obtained Application of the CAI (Computer Assisted Instruction) method in the learning process can provide convenience in the learning process. Where the form of learning is more orderly and easy to access.